Knowledge, Attitudes, and Clinical Practices of Dental Professionals during COVID-19 Pandemic in Pakistan - Almas, Khalid; Khan, Abdul Samad; Tabassum, Afsheen; Nazir, Muhammad Ashraf; Afaq, Ashar; Majeed, Abdul (European Journal of Dentistry, 2020)
Objective The aim of this study is to assess knowledge, attitudes, and clinical practices of dental professionals regarding the prevention and control of coronavirus disease 2019 (COVID-19) in Pakistan.Materials and Methods General dentists and dental specialists working in public and private dental practices, hospitals, and academic institutions participated in this cross-sectional study. A pilot-tested questionnaire was sent to dental professionals through an online link in Pakistan and data collection was completed in April-May 2020. The knowledge score was calculated from 22 variables about the COVID-19.Results The study included data of 343 dental professionals with 47.2% of males and 52.8% of females. The mean knowledge score was 16.78 ± 2.25, and it significantly differed between general dentists (16.55 ± 2.36) and dental specialists (17.15 ± 2.04) (p = 0.020), and those with up to 10 years of experience (16.58 ± 2.28) and those with more than 10 years of experience (17.05 ± 2.2) (p = 0.026). Only 15.5% of the participants were comfortable in treating patients during the COVID-19 pandemic. A workshop/seminar on the COVID-19 was attended by 23% of the participants. In multivariate analysis, being comfortable in treating patients (odds ratio = 3.31, 95% confidence interval = 1.63, 6.73) was associated with the attendance of workshop/seminar on COVID-19.Conclusions Dental professionals had adequate knowledge about COVID-19, but a few of them were comfortable in treating patients during the pandemic. A minority of dental professionals attended a workshop/seminar on the COVID-19. Continuous education activities should be provided to dental professionals to enhance their role in the prevention of COVID-19 spread and promotion of oral health.
Keywords: COVID-19; pandemic; dental professionals; continuing education; awareness